Educational games for language learning - Vlasenko, Ludmila; Sulima, Irina (My University, 2011)
This article reveals the basic features of teaching educational games; educational games are analyzed and attention is concentrated on the importance of their development in the teaching of students.
Keywords: комунікативна компетентність; навчальна гра; мовленнєва діяльність; коммуникативная компетентность; обучающая игра; речевая деятельность; communicative competence; educational game; communicative activity; кафедра ділової іноземної мови та міжнародної комунікації